GENETIC ASPECTS IN THE GENERATION OF OIL ALKANES - Semkin V.I. (My University, 2006)
Genetic aspects of the generation of oil alkanes suggest that the genesis of oils is controlled by a succession of factors of a single genetic chain, which indicate that the possible sources of oils are certain inorganic components of magmatic fluids, the mineral matter of sedimentary rocks, and the biomass of anaerobes, which is formed when magmatic fluids filter through marine and offshore sedimentary deposits. © Pleiades Publishing, Inc. 2006.